Influence of external magnetic field on intensity and directivity of EUV radiation from high-current pulse plasma diode - Borgun, Ie.V.; Azarenkov, N.A.; Hassanein, A.; Tseluyko, A.F.; Maslov, V.I.; Ryabchikov, D.L.; Grechko, Y. (Вопросы атомной науки и техники, 2012)
This work is devoted to evaluate the influence of the additional external magnetic field on dynamics of the radiation in the extreme ultraviolet (EUV) range from multi-charged tin plasma of high-current pulse diode. Investigations have shown that the use of an additional external magnetic field has improved the stability of the plasma diode, enhanced the intensity of radiation, and changed the radiation profile.